2002
DOI: 10.1002/macp.200290025
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic Transitions in Polydiacetylene Langmuir‐Blodgett Films due to Molecular Recognition at the Film Surface Studied by Spectroscopic Methods and Surface Analysis

Abstract: Langmuir‐Blodgett films of polydiacetylene are used to create a biosensor on the basis of a surface host‐guest recognition process. Functionalizing a 10 wt.‐% fraction of the diacetylene monomer with biotin leads to a visually observable color change in the resulting polymerized film when streptavidin in the molar ratio streptavidin:biotin = 1:2 is added. The chromatic transition, caused by a shortening of the conjugation length of the π‐electron system in the polydiacetylene backbone, is investigated by monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…PDA is a class of amphiphilic lipid polymers known for their unique blue-to-red color transitions in response to stimuli such as high pH, 15,16 high temperature, [17][18][19] and molecular binding events. 20,21 These chromatic properties have resulted in the popular use of PDA in a range of colorimetric biosensing applications in the form of liposomes, [22][23][24] Langmuir-Blodgett films, 25,26 strips, [27][28][29] and others. 30,31 The additional fluorescence "turn-on" characteristic of redphase PDA is attributable to its use in the development of fluorescence-based sensors.…”
Section: Introductionmentioning
confidence: 99%
“…PDA is a class of amphiphilic lipid polymers known for their unique blue-to-red color transitions in response to stimuli such as high pH, 15,16 high temperature, [17][18][19] and molecular binding events. 20,21 These chromatic properties have resulted in the popular use of PDA in a range of colorimetric biosensing applications in the form of liposomes, [22][23][24] Langmuir-Blodgett films, 25,26 strips, [27][28][29] and others. 30,31 The additional fluorescence "turn-on" characteristic of redphase PDA is attributable to its use in the development of fluorescence-based sensors.…”
Section: Introductionmentioning
confidence: 99%
“…To date, analyte-specific PDA sensors are mostly developed in the form of a liposome (also referred to as a vesicle) in aqueous solutions [11] , [18] , [19] or a deposited layer on rigid substrate surfaces [20] , [21] , [22] , [23] . However, due to complex sample handling requirements (e.g., multiple pipetting) and high costs of fabrication, these forms are not always ideal for biosensing applications in remote areas or resource-limited settings, which would most benefit from PDA’s instrument-free and naked-eye detection.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have investigated the underlying mechanism behind the observed fluorescence switching, 5b,5g–5j,13 and much of the evidence suggests that this switching is the result of mechanical stress on the PDA structure caused by binding to EpCAM. Such external stresses on the PDA structure are known to trigger electronic transitions in the delocalized π-electron networks of the PDA backbone and thereby change the optical properties.…”
mentioning
confidence: 99%
“…In this model, radiative transition (decay) from a higher excited Ag symmetry state (dipole-forbidden) to the lowest excited Bu state (dipole-allowed) is believed to be responsible for shifting the fluorescence wavelength from short (blue) to long (red). 5b,5g–5j,13 We would therefore suppose that direct mechanical interaction between the ACP probes and EpCAM is a necessary requisite for fluorescence switching to occur.…”
mentioning
confidence: 99%